The stage of drawing : gesture and act : selected from the Tate Collection - Newman, Avis; De Zegher, Catherine; Bonnefoy, Yves; Bryson, Norman; Fisher, Jean; Newman, Michael (New York : Tate publishing and Drawing Center, 2003)
Arp, Hans (Jean) ; Artaud, Antonin ; Bacon, Francis ; Beckmann, Max ; Bonnard, Pierre ; Fautrier, Jean ; Flanagan, Barry ; Fuseli, Henry S. Füssli ; Giacometti, Alberto ; Hamilton Mortimer, John ; John, Gwen ; Penone, Giuseppe ; Reynolds, Joshua ; Rigby, Elizabeth
The stage of drawing : Gesture and act - Selected from the Tate Collection, The Drawing Center, New York, April 5-May 31, 2003
The stage of drawing : Gesture and act - Selected from the Tate Collection, Museum of Contemporary Art, Sydney, June 18-August 24, 2003
The stage of drawing : Gesture and act - Selected from the Tate Collection, Tate Liverpool, Liverpool, September 26, 2003-March 28, 2004
boek